STRATEGIES TO STRENGTHEN WORK CULTURE THROUGH THE IMPLEMENTATION OF ETHICAL LEADERSHIP AND SERVANT LEADERSHIP IN THE AUTOMOTIVE MANUFACTURING INDUSTRY (Case Study on PT. Mitsubishi Electric Automotive Indonesia) - Marlia Adityawati (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze strategies for strengthening work culture through the implementation of ethical leadership and servant leadership at PT. Mitsubishi Electric Automotive Indonesia, and to identify the challenges and contributions of these two leadership styles to strengthening work culture in the automotive manufacturing industry. This study used a qualitative approach with a single case study method. Data were collected through in-depth interviews with 10 informants consisting of management level, supervisors, and production line employees. Participatory observation was conducted over three weeks, supported by analysis of company documents. Data analysis used direct interview methods and in-depth observation. The results of the study revealed five main implementation strategies: (1) leaders exemplifying ethical behavior; (2) employee empowerment through delegation of authority; (3) developing two-way communication mechanisms; (4) creating a supportive and family-like work environment; and (5) integrating ethical values into the performance management system. The dimensions of family atmosphere and identification with the leader were identified as key success factors in Indonesia's collectivist cultural context. Key challenges include resistance to change, measuring short-term impact, and consistency amidst production pressures. This study recommends integrating ethical values and servant behavior into recruitment systems, developing ethics-based leadership training programs, and designing performance management systems that balance quantitative targets with ethical behavior assessments. This study is the first to integrate ethical leadership and servant leadership within a framework for strengthening work culture in the automotive manufacturing industry, with specifically case study in PT. Mitsubishi Electric Automotive Indonesia and identifies the family atmosphere dimension as a novel finding within a collectivist cultural context.